Impact Millennial Road Safety Festival Social Campaign Program Korlantas Polri to Changing Drive Teenager's Behavior in Indonesia - Albertus Wahyurudhanto; Ilham Prisgunanto (Journal of Indonesia Road Safety, 2020)
Millennial Road Safety Festival (MRSF) was the one of social campaign Korlantas Polri to give information about safety riding in 2019 in 34 provinces in Indonesia. This research would measure the impact of MRSF on changing drive teenager's behavior in safety riding. Theoretical studies of this research use Cultivation theory from George Gerbner, Uses, and Gratifications theory from Palmgreen dan Rosengreen, and Reaction and Action from Lee for psychology in behavior. Research methodology uses quantitative data analysis for 254 respondents from Polda Metro Jaya 31 respondents, Polda Bali 30 respondents, Polda Jawa Barat 51 respondents, Polda Sulawesi Selatan 41 respondents, Polda Jawa Timur 30 respondents. Finding research talk there were impact MRSF to changing drive teenager's behavior safety reading. The most substantial factor MRSF program for planning media management is the weakness factor for communicator int's mean anchors of MRSF program television. ABSTRAK Millennial Road Safety Festival (MRSF) merupakan salah satu bentuk kampanye sosial Korlantas Polri untuk memberikan informasi seputar safety riding di tahun 2019 pada 34 provinsi di Indonesia. Penelitian ini akan mengukur dampak MRSF terhadap perubahan perilaku berkendara remaja dalam safety riding. Kajian teori dalam penelitian ini menggunakan teori Cultivation dari George Gerbner, teori Uses, and Gratifications dari Palmgreen dan Rosengreen, dan Reaction and Action dari Lee untuk psikologi dalam perilaku. Metodologi penelitian menggunakan analisis data kuantitatif sebanyak 254 responden dari Polda Metro Jaya 31 responden, Polda Bali 30 responden, Polda Jawa Barat 51 responden, Polda Sulawesi Selatan 41 responden, Polda Jawa Timur 30 responden. Berdasarkan hasil penelitian ditemukan dampak MRSF terhadap perubahan perilaku membaca keselamatan remaja drive. Faktor yang paling substansial dari program MRSF untuk perencanaan pengelolaan media adalah faktor kelemahan dari sarana jangkar rata-rata komunikator int di televisi program MRSF.